Cameroon : First Review Under the Extended Credit Facility Arrangement Requests for Waiver of Nonobservance of a Performance Criterion and Modification of Performance Criteria-Press Release; Staff Report; Supplementary Information; and Statement by the Executive Director for Cameroon. (IMF Staff Country Reports; Country Report ;, 2018)
This paper discusses Cameroon's First Review Under the Extended Credit Facility (ECF) Arrangement, Requests for Waiver of Nonobservance of a Performance Criterion (PC) and Modification of PCs. Cameroon's performance under the three-year ECF-supported program approved in June has been satisfactory, with the fiscal and external adjustments contributing to the rebuilding of buffers. Growth in 2017-18 is expected to be somewhat weaker than anticipated in the program, declining to 3.7 percent in 2017 owing to lower oil production and tepid demand, with a recovery to 4.2 percent in 2018. The medium-term outlook remains positive, boosted by the coming on stream of large energy and transport infrastructure projects.